Major factors underlying the academic performance of underachievers at UiTM Cawangan Sarawak, Kampus Samarahan: student perspective/ Yuthandy Maniam ... [et al.] - Maniam, Yuthandy; Bujang, Fatimah; Ramakrishnan, Prabha; Caroline, Elizabeth (2009)
This study was carried out for the express purpose of determining the major academic and non-academic factors that directly or indirectly contribute to the inability of some of the students at UiTM Sarawak to meet the minimum academic requirement to continue their diploma studies, which is a CGPA of 2.0. The study investigated this phenomenon from the perspective of the students' own perception of the difficulties that they face. Four categories in the academic domain and three categories in the non-academic domain were identified for the study. They were teaching, learning, assessment and academic support categories for the academic domain and self-management, personal problems and non-academic support categories for the non-academic domain. Data for the study was collected from ninety four students using a questionnaire consisting of 240 items covering various aspects of the seven categories. The study enabled the researchers to identify various academic and non-academic factors that in the opinion of the students could have contributed to their underachievement. It is hoped that the recommendations made in chapter five would prove useful to the management of UiTM Sarawak in their relentless efforts at helping students who face difficulties in their studies and consequently at producing greater numbers of students who successfully complete their diploma studies each semester.